Urethroplasty in the Management of Urethral Stricture - Singh, Joginder; Sidhu, Bholla Singh (Indian Journal of Plastic Surgery, 1975)
1. Twelve of the 22 patients admitied with stricture urethra and treated by urethroplasty procedures are reported.2. Local skin flap procedure is preferable to meatotomy in meatal stricture.3. Excision anastomosis is ideal where feasible while urethroplasty for stricture of the penile urethra is both satisfactory and easy.4. In aged and bad risk patientif a proximal urethrostomy can be fashioned a good functional result ensues.5. Attention is drawn to the apparently neglected problem of stricture urethra in this country. And it is stressed to undertake more of the urethroplasty procedures rather than to subject all patients to bouginage.